2023
DOI: 10.21834/ebpj.v8i23.4462
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Positive Psychological Factors for Sustainable EFL Learning

Abstract: The purpose of this study was to explore the relationship between foreign language enjoyment, grit, and English language performance. This study adopted a descriptive correlational research design involving 388 Chinese EFL university students. Self-reported questionnaires and the College English Test-Band 4 were utilised to collect the data. The findings reported a moderate to high level of language enjoyment and grit among the students. No significant differences were found between male and female students re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Research of FLA in SLA began to flourish (MacIntyre, 2017). FLCAS has been commonly utilized in China to measure Chinese foreign language learners' FLA, and many studies concluded that Chinese EFL learners are of moderate to high levels of FLA (Li, 2020;Naudhani et al, 2018) Most studies have focused on the negative influence of FLA on language learning and have viewed anxiety as a barrier to SLA (Hu et al, 2023). Accordingly, much research has been conducted to explore the sources of FLA (Li & Li, 2016;Oad, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research of FLA in SLA began to flourish (MacIntyre, 2017). FLCAS has been commonly utilized in China to measure Chinese foreign language learners' FLA, and many studies concluded that Chinese EFL learners are of moderate to high levels of FLA (Li, 2020;Naudhani et al, 2018) Most studies have focused on the negative influence of FLA on language learning and have viewed anxiety as a barrier to SLA (Hu et al, 2023). Accordingly, much research has been conducted to explore the sources of FLA (Li & Li, 2016;Oad, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%